Lines of thought drawing from Michelangelo to now - Seligman, Isabel ca. 20. Jh (Thames & Hudson, 2016)
Looking at works from a range of different artists and their various approaches, this book examines the process and practice of drawing, showcasing artworks from 15th- and 16th-century masters right up to artists working today. In arranging them not by period or style, but by the types of thinking that give rise to them, readers gain fresh insights into the thought processes of some of the world's greatest artists. This thematic rather than chronological structure allows us to place historical drawings side-by-side with modern and contemporary works, to show how artists from widely differing times and places have all used drawing to record, explore and develop ideas. The accompanying exhibition, 'Lines of Thought: Michelangelo to Bridget Riley. Drawings from the British Museum', will tour to venues associated with art schools around the UK, and internationally, to inspire students to draw. The exhibition and this book include highlights of the British Museum's Prints and Drawings collection, as well as some lesser-known contemporary works. Exhibition: Poole Museum and Art Gallery, Great Britain (3.09. - 06.11.2016) / The Brynmor Jones Library Art Gallery, University of Hull, Great Britain / Ulster Museum, Belfast, Great Britain